Data Mining Approach on Nationwide School Exam System - ONG Wai Kit, Janson Luke; Asirvadam, Vijanth S.; Krishnan, Suresh K. (2004)
Knowledge discovery (or data mining approach) for nationwide school exam prototype system not only adds value to the information readily available but it also assist decision-makers to make decision based on the new information. This approach can even include the ability to model and remodel the data from large database. Knowledge discovery for school exam system usage and benefits includes, locating the right information, presenting of information (reports, graphs), discovery of information (which the paper will emphasis), and possible new trend forecasting.